Gastrointestinal and Hepatic Manifestations in Patients with Covid-19 - Thapa, Bhawesh; Basnet, Bhupendra Kumar; Poudyal, Nandu Silwal; Shrestha, Ramila; Khanal, Kiran Kumar; Baral, Ram Krishna (Journal of Advances in Internal Medicine, 2023)
BACKGROUND Gastrointestinal symptoms and Liver injury have been frequently described in patients with COVID-19.In this study, we aim to study the prevalence of Gastrointestinal symptoms and Liver injury and their impact on disease severity and clinical outcomes.METHODS This is a descriptive, cross sectional observational study done in 195 patients admitted to Bir Hospital with Corona virus Disease-19(COVID-19) from May 2021 to July 2021.Patients presenting symptoms and liver function tests (LFTs) were noted at admission. Gastrointestinal symptoms were defined as the presence of one of Nausea, Vomiting, Abdominal pain or Diarrhea. Liver injury was defined as elevation of Total Bilirubin > 1mg/dl or Alanine transaminase (ALT) >40U/L, Aspartate Transaminase(AST) >40U/L or Alkaline Phosphatase(ALP)>135 U/L. Patients were followed during hospitalization and outcomes assessed at discharge.RESULTS Gastrointestinal symptoms were present in 32.3% among which Nausea (27.7%) was the commonest. There was no significant association of Gastrointestinal symptoms with duration of hospital stay, ICU admission or mortality. Liver injury was present in 72.8% patients and significantly more in those with GI symptoms than without GI symptoms. Patients with liver injury had a significantly longer hospital stay (8.92 ± 3.7 days vs 6.70±3.2 days, p=0.004), higher ICU admissions (38.02% vs 7.54% p=0.000018) and mortality (23.23% vs 1.88%, p=0.001) compared to patients with normal LFTs.CONCLUSION Gastrointestinal symptoms and Liver Injury are common in patients with COVID-19. Liver injury at admission is associated with severe disease and higher mortality. More attention should be given in the care of such patients to avoid poor outcomes.